A superação da pobreza através da distribuição justa das riquezas sociais: uma análise da consistência teórica do Programa Bolsa Família e das perspectivas dos beneficiários de saída autosustentada do programa - Sousa, Juliane Martins Carneiro de (2009)
Bolsa Família is the major brazilian conditional cash transfer program. It provides money to poor families contingent on investments in human capital, such as sending children to school or bringing them to health centers. This work aims to investigate if this program, in its normative structure, can be considered an appropriate policy of income redistribution and if it is able, appliances of the Welfare State model in the brazilian society and to approach the program in two different ways: as an alternative to more traditional social assistance programs and as a demand-side complement to the supply of other social needs. We will work on the thesis that the program by itself can not provide vulnerable populations with enough means to overcome poverty and to participate effectively on the market. According to this assumption, this paper is going to consider the reasons why tackling income necessary, along with the program, that the Government - in both federal and local spheres shall place major investments in critical areas like education and health.